Temporal legacies of coal mining in the West Coast, New Zealand: path-dependency or path-creation? - Sean Connelly; Etienne Nel; Alison Floyd (Environmental Research: Energy)
Global energy transition and decarbonisation efforts in the face of climate change present a new challenge for coal-based resource communities. While many resource-based communities and coal mining communities have become accustomed to the boom-bust cycles of resource extraction, the transition to alternative energy sources presents unique challenges to coal mining communities. In this paper, we document the long process of transition in the coal mining town of Blackball in New Zealand. Blackball has a long history of mining, yet it is also a community where the local mines on which the town depended have been closed for 50 years. The legacy and heritage of coal mining has since shaped efforts at diversification and revitalization, highlighting the tensions between path-dependency and new path creation in the shaping of the future of Blackball. We draw on concepts from evolutionary economic geography to highlight how iterative processes of path creation and path dependency have played out and identify the important role of community agency and external support in mediating those processes. The temporal component of Blackball’s coal transition presents useful lessons for other mining communities which currently face closure.